Analisis Break Even Point (BEP) sebagai Dasar Penentuan Kelayakan Usaha pada Cafe Akademos Warungdowo - Herlina Widya Ananta; Dessy Boegiyati (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
This study aims to analyze the Break Even Point (BEP) as a basis for determining business feasibility at Cafe Akademos Warungdowo using a descriptive quantitative approach and case study method. Data were collected through interviews, observations, and documentation of financial reports during the period of April 16–May 15, 2026. The analysis included calculations of fixed costs, variable costs, contribution margin, Weighted Average Contribution Margin Ratio (WA-CMR), Break Even Point (BEP), Margin of Safety (MoS), and profit-loss reports. The results showed that the café’s total fixed costs amounted to Rp1,300,000, with total sales of Rp3,945,000 and a contribution margin of Rp1,376,760. The WA-CMR value was 34.90%, while the BEP was achieved at sales of Rp3,725,051 or 762 product units. Actual sales of 806 units exceeded the break-even point, resulting in a net profit of Rp76,760 Although the business was considered financially feasible, the Margin of Safety (MoS) Ratio of 5.58% indicates that the business remains vulnerable to declining sales. Therefore, the café management needs to improve profitability through cost efficiency, price evaluation, and optimization of products with high contribution margins.